Proses Penanganan Administrasi Delivery Order Peti Kemas pada Badan Usaha Pelabuhan Batam - Monika Safitri Aritonang; Nurmaliana Sari Siregar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to conduct an in-depth analysis of the administrative process for container Delivery Order (DO) handling implemented at Batu Ampar Port, Batam. The primary focus is to identify the procedural stages and evaluate the obstacles encountered during the DO issuance process. The Delivery Order is a crucial import document that serves as a transit permit, enabling service users to retrieve imported goods from the port area. The research methodology employs field research (field research) supported by a literature review (library research), allowing for the practical and thorough collection of operational data. The findings indicate that the administrative DO handling workflow commences with the receipt of documents from the shipping company representatives or service users, followed by the segregation of documents based on the company, recording the number of DOs, and culminates in the printing and validation of Form 2B, which serves as the official proof of cargo collection. This entire process demands close coordination among work units, particularly the administration and container depot sections. The study concludes that the effectiveness of DO management significantly impacts the smooth distribution of imported goods from the port. Common constraints frequently encountered include data inconsistency between the Bill of Lading and the received DO, as well as limitations in facilities and human resources within the administrative process. Recommended solutions include increasing supervision and refining the communication system between the applicant and the officials to ensure that the DO issuance process proceeds smoothly, promptly, and in compliance with established procedures.